2004
DOI: 10.4322/rbcv.2014.359
|View full text |Cite
|
Sign up to set email alerts
|

Biologia reprodutiva da tabarana Salminus hilarii (osteichthyes, characidae) na represa de Três Marias

Abstract: ResumoEste trabalho teve como objetivo estudar a biologia reprodutiva da tabarana Salminus hilarii, na represa de Três Marias (MG). Foram determinados, a partir de exemplares capturados durante 20 meses, os seguintes parâmetros: comprimento padrão (CP), peso corporal (PC), índices gonadossomático (IGS), hepatossomático (IHS), de gordura abdominal (IGA) e estágio de maturação (em repouso, em maturação, maduro ou esgotado). Verificou-se que o período de reprodução da tabarana se concentra nos meses finais e inic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 1 publication
1
15
0
3
Order By: Relevance
“…Slightly different intervals were observed in the Sorocaba River (Takahashi, 2006), in the Mogi Guaçu River (Godoy, 1975) and in the Três Marias reservoir, in Minas Gerais (Andrade et al, 2006), but these were included in the period observed in the present study.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Slightly different intervals were observed in the Sorocaba River (Takahashi, 2006), in the Mogi Guaçu River (Godoy, 1975) and in the Três Marias reservoir, in Minas Gerais (Andrade et al, 2006), but these were included in the period observed in the present study.…”
Section: Discussionmentioning
confidence: 69%
“…Subsequent monitoring of the juveniles until maturation showed, for the first time, that S. hilarii males and females become mature at one year and two years old, respectively. Previous studies had only been able to base maturity (not first maturation) on total length (Nakatani et al, 2001;Andrade et al, 2006) due to the wild origin of the animals.…”
Section: Discussionmentioning
confidence: 99%
“…Zaiden (2000), para Brycon hilarii, considerou repouso, maturação I, maturação II, maduro e regressão. Em Piracanjuba, observaram-se 4 está-dios de maturação: Repouso, Maturação Inicial, Maturação Avançada e Regressão (Ganeco et al 2001) e Andrade et al (2004) classificaram quatro estádios de maturação para a tabarana na represa de Três Marias: recuperação-repouso, em maturação, maduro e esgotado.…”
Section: Discussionunclassified
“…The presence of hooks on fins has been reported in various species of characins, including other Astyanax species (Andrade et al, 1984;Andrade et al, 2004;Porto-Foresti et al, 2005), and is considered a temporary secondary sexual characteristic which appears only in males, generally, during the reproductive period (Ihering & Azevedo, 1936). According to Malabarba & Weitzman (2003), the presence of hooks on fins in adult males is a synapomorphy of the clade that includes the Gasteropelecidae, Serrasalmidae, and Characidae, and Mirande (2010) considers the absence of hooks as being a plesiomorphic character.…”
Section: Discussionmentioning
confidence: 99%